Redescription and lectotype designation of Helichus cordubensis Berg (Coleoptera: Dryopidae) - Rodriguez, G. A.; Manzo, V. (Zootaxa, 2012)
Helichus cordubensis Berg, 1885 is redescribed based on type material and new material. A lectotype is designated for this species. Male genitalia are illustrated for the first time.